Olfactory mucosal mesenchymal stem cells delivered by gelatin sponge scaffolds promote functional recovery of spinal cord injury - Li, Wenshui; Jiang, Xinchen; Lu, Shuo; Lu, Wen; Ma, Shanshan; Zhuo, Yi; Gao, Qingtao; Xiao, Yi; Wu, Binqian; Xie, Junyang; Yu, Yuhang; Li, Xiangxin; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Spinal cord injury (SCI) is a pathological condition that damages the central nervous system. Due to the persistence of neuroinflammation after injury, the prognosis is often poor. Recent studies have found that local transplantation of mesenchymal stem cells (MSCs) can improve SCI. However, MSCs retain and engraft at the injured site limit, which may be the reason their effectiveness is greatly reduced. A gelatin sponge (GS), commonly used in clinical practice, was selected as a scaffold to deliver olfactory mucosal mesenchymal stem cells (OM-MSCs). This was done to to enhance local reparative of MSCs at the injury site. We also paid special attention to the biocompatibility of GS co-cultured with OM-MSCs in vitro, and then applied acellular GS and GS loaded with OM-MSCs to the rat SCI model, respectively. After the scaffold was transplanted into rat complete spinal cord injury, behavioral scores and hindlimb movement scores were improved evidently. Local inflammation in the spinal cords of transplanted rats was reduced, and the changes were related to cell pyroptosis. In addition, we found that gelatin sponges and OM-MSC transplantation did not damage other organs in rats. In conclusion, the GS scaffold loaded with OM-MSCs can reduce the local inflammatory microenvironment and facilitate neurological recovery, providing a potential and practical strategy for therapeutic approach of spinal cord injury.